2019
DOI: 10.1111/liv.14298
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of large, middle and small hepatitis B surface proteins in HBeAg‐positive patients treated with peginterferon alfa‐2a

Abstract: Abbreviations: aa, amino acid; ALT, alanine aminotransferase; AUC, area under the curve; CHB, chronic hepatitis B; CI, confidence interval; ELISA, enzyme-linked immunosorbent assay;HBeAg, hepatitis B e antigen; HBs, hepatitis B surface (protein); HBsAg, hepatitis B surface antigen; HBV, hepatitis B virus; LAM, lamivudine; LLOQ, lower limit of quantification;PegIFN, peginterferon alfa-2a; qHBsAg, quantitative hepatitis B surface antigen; ROC, receiver operating characteristic; SC, seroconversion; SHBs/MHBs/LHBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Most researches on HBsAg focused on the function of the small surface protein of HBsAg. PreS antigen (preS1Ag+preS2Ag) is the N-terminal extension of small surface protein, and the preS antigen, as well as middle and large surface proteins, have gained widespread attention in recent studies on the role of oncogenic risk factors [6], identification of inactive HBV carriers [10], prognosis of therapeutic response [12], and prediction value of HBV infection phases and virological response [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researches on HBsAg focused on the function of the small surface protein of HBsAg. PreS antigen (preS1Ag+preS2Ag) is the N-terminal extension of small surface protein, and the preS antigen, as well as middle and large surface proteins, have gained widespread attention in recent studies on the role of oncogenic risk factors [6], identification of inactive HBV carriers [10], prognosis of therapeutic response [12], and prediction value of HBV infection phases and virological response [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has a transcriptional transactivator function [8] and contains binding sites for fibronectin, transferrin, and polymerized human serum albumin (pHSA) [9], which are associated with virus entry, release, and active replication. Besides, some studies have shown that the amount and proportions of HBsAg components could be used to identify inactive HBV carriers [10], OBI [11], and predict the response to antiviral therapy [12]. Considering the fact that there have been few reports on clinical preS2Ag detection, it is essential to develop a rapid and quantitative method for preS2Ag.…”
Section: Introductionmentioning
confidence: 99%
“…Mit PD Dr. Florian van Bömmel und Prof. Dr. Thomas Berg, Leipzig, wurden neue klinische Biomarker identifiziert, die eine erfolgreiche Therapie bei chronisch HBV-Infizierten anzeigen [ 55 ] und zur Identifizierung von „inaktiven chronischen HBV-Trägern“ beitragen können [ 56 ]. Weitere HBV-relevante Biomarker wurden in Zusammenarbeit mit Prof. Dr. Markus Cornberg und Prof. Dr. Heiner Wedemeyer, Hannover, analysiert [ 57 , 58 ].…”
Section: Nationale Und Internationale Kooperationen Sowie Bereitstell...unclassified
“…An alternative ELISA-based method (HBV NRAg; Beijing Wantai Biological, Beijing, China) has been developed to qualitatively detect the PreS1 antigen and HBcAg, with the former having shown surrogate utility for HBV cccDNA activity and HBV replication [ 90 , 91 ]. Furthermore, the measurement of PreS1, or L-HBsAg, using calibrated ELISA assays, has been described in several studies to be associated with detection of residual serum HBV DNA [ 92 ], differentiation of active and inactive CHB, and prediction of functional cure via L-HBsAg to M-HBsAg ratios [ 93 , 94 ], although L-HBsAg levels differ by HBV genotype [ 95 ] which may confound predictive interpretation in diverse populations. The combined detection of conserved amino acid regions within both antigens [ 96 ], which has been termed ‘nucleic acid-related antigen’ [ 97 ], is performed through a dual sandwich ELISA with antigen specific monoclonal antibodies [ 98 ].…”
Section: Novel Hbv Biomarkersmentioning
confidence: 99%